Analisis Penanganan Anak Cerdas Istimewa Dan Specific Learning Disability ( Diskalkulia, Disgrafia, Disleksia) - Rafael Lisinus Ginting; Elpani Br Sinurat; Kesiana Br Pasaribu; Maysarah Chan; Nita Febriani Gulo; Raihan Zaki Altiaz; Widia Andriani Putri (Lembaga Pengembangan Kinerja Dosen, 2023)
Exceptionally gifted children possess extraordinary potential; however, addressing their needs optimally often presents a challenge. On the other hand, specific learning disabilities such as dyslexia, dysgraphia, and dyscalculia pose specific obstacles in the learning process for children. The aim of this research is to facilitate readers in understanding the core aspects related to the Analysis of Handling Exceptionally Gifted Children and Specific Learning Disabilities such as Dyslexia, Dysgraphia, and Dyscalculia. This research employs a library research methodology.The findings of this research encompass several interventions applicable to students with learning disabilities. One form of learning service for special needs children involves providing treatment to overcome the difficulties and learning barriers they face. The role of media is crucial in education, as it can effectively aid in conveying information from learners to the subject matter.